Industrial Relations in the Digital Age: Dynamics, Challenges, and Opportunities - Herwina, Naila; Syamsuri, Abd. Rasyid (International Journal of Economic, Business & Applications, 2025)
The digital era has brought significant changes in the dynamics of industrial relations, creating various challenges as well as new opportunities. This article examines the dynamics of industrial relations in the digital era with a focus on digital transformation in dynamic industrial relations, looking at the challenges of industrial relations in the digital era, presenting significant challenges especially in labor management, while opening up significant opportunities for innovation and adapting industrial relations opportunities in the digital era. This article uses a literature review approach to analyze the Influence, Dynamics, Challenges, and Opportunities of industrial relations in the digital era. The results show that national industrial policies that focus on regulations and incentives still rely on traditional sectors, making them less prepared to face digital transformation and global competition.